The Semantic Analysis of Slang in The Movie “School” - Madazizova Dilafruz Habibiloyevna (Zien Journals, 2021)
The given article is about the notions of scholars about slang and the reasons of using them, it’s classification, it’s popularity among the youth and it’s semantic analyzes according to the movie “School” produced by Uzbek filmmakers.
Keywords: slang; classification of slang; reasons of using slang; teenagers